(untitled) (Malaysian Management Journal, 2019)
The purposes of this study are to address the current solid waste management (SWM) issues and to evaluate the best available practices that can be adopted to develop a holistic, integrated, effective and a sustainable SWM system in Malaysia. The idea is to analyze and to evaluate the weaknesses of the current practice of â€œextract-make-use-disposeâ€ linear economic (LE) model that causes depletion of natural resources, massive increase in the generation of solid waste, severe degradation of the environment and a substantial cost to manage. These results will be synthesized to establish critical gaps to benchmark against the new economic model of a circular economy (CE) that works on a closed-loop system of reducing, reuse and recycle (3R). CE aims to efficiently utilize the resources to allow for maximum reuse through refurbishment, remanufacturing and recycling which will minimize the wastages for disposal. This study employs a literature review to identify relevant practices of a circular business model that can potentially be adopted, a life-cycle (LC) analysis to assess the environmental impacts and a study on waste characteristic and its composition to determine the waste fraction and the amount of energy contained in the solid waste. This paper gives an insight into the possibility of embracing the concept of a CE alongside with a suitable treatment and disposal technologies to develop a sustainable SWM system in Malaysia. This holistic approach would able to minimize the waste through waste prevention, to maximize the economic return through reuse, recycle and recovery, to give the protection to the environment and to improve the quality of life.